How has microcredit supported agriculture? Evidence using panel data from Bangladesh. (20th August 2015) - Khandker, Shahidur R.; Koolwal, Gayatri B.
Abstract: Improving agricultural productivity has received a greater attention in recent years amid concerns about rising food insecurity, population pressures, and climate change. Many believe that better access to institutional credit, spanning microcredit as well as commercial and agricultural banks, can help rural households smooth risks, and access inputs and other technology to modernize agriculture and improve farm/nonfarm linkages. We use recently augmented household panel data spanning over 20 years in Bangladesh to examine the effects of rural credit expansion (both microcredit and formal bank channels) on outcomes for agricultural households. We find that microcredit has benefited households with lower landownings, raising agricultural income from activities such as livestock rearing that require less land, as well as nonfarm income diversification for all households, but with the strongest effect for landless or near‐landless households. We do not find effects of microcredit on crop income, but do, however, find that reported supply‐side credit constraints significantly lower crop income. Borrowing by both men and women has contributed to nonfarm income growth for marginal farmers, but only men's borrowing has contributed to nonfarm income growth among higher landowning groups.